(3eMGSHI GdHfhc (B/s - (3TbjQ, aGFbs ((3GdCQOf(B: s (3OGQ GdeSjQI(B, s, 2000)
(3JLO aj gPG GdcJGH GdLgGR GdeUQaj , bSe GdNRjfI , bSe GdMSGHGJ GdLGQjI ,bSe dhOGFY ,GdSda hGdbQhV ,bSe GdcaGdGJ, GdcaGdGJ hNWHGJ GdVeGf ,GdEYJeGOGJ hHhGdU GdJMUjd , bSe GdMhGdGJ ,bSe GdYedjGJ GdNGQLjI , bSe GdChQGb GdNGQLjI , bSe GdChQGb GdeGdjI , bSe GdMGSHGJ GdYGeI ,GdETQGa hGdQbGHI , GdHfhc hGdeUGQa GdESdGejIs
(3GdeQGLY U(B.364s
Keywords: (3GdChQGb GdeGdjIs; (3GdHfhcs; (3GdeMGSHIs